Key performance indicators for success in the 2024 Olympic men's basketball tournaments - Tomanek, L.; Suja, Š.; Selmanovic, A.; Vencurik, T. (Journal of Human Sport & Exercise, 2025)
The purpose of the present study was to examine differences between winning and defeated basketball teams in the 2024 Men's Olympic Tournament (OT) (n = 26) and the 2024 Olympic Qualifying Tournaments (OQT) (n = 36). The differences were assessed in three selected indicators: 3-point percentage (3PT%), rebound percentage (REB%), and turnover percentage (TOV%). T test has shown significant differences in 3PT% (p < .01) and REB% (p < .01) at OT. In OQT, we found statistically significant differences between winning teams and defeated in all variables (p < .01). Binary logistic regression identified in OQT all three independent variables as significant predictors of winning. If 3PT% and REB% increased by one unit, the odds of winning increased by 13% and 29%, respectively. On the other hand, if TOV% increased by one unit, the odds of winning decreased by 24%. In the OT, the binary logistic regression identifies only REB% as a significant predictor of winning. One unit of increase in REB% was associated with a 25% greater chance of winning. Coaches should focus on 3-point shooting efficiency, rebounding control, and minimizing turnovers, as these factors significantly affect the likelihood of winning basketball games.